Terbutaline in children with asthma - Leegaard, Jens (1973)
A double-blind, single-dose trial was carried out on 30 asthmatic children to study the effect of oral terbutaline in two different concentrations and of a placebo on ventilatory function and pulse rate. The higher dose of terbutaline (0·075 mg/kg) gave a satisfactory and prolonged action on ventilation without cardiovascular side effects.